Attitudes of Healthcare Providers towards Non-initiation and Withdrawal of Neonatal Resuscitation for Preterm Infants in Mongolia - McAdams, Ryan M; Erdenebileg, Ariuntsatsral; Batra, Maneesh; Gerelmaa, Zagd (Journal of Health, Population and Nutrition, 2012)
Antenatal parental counselling by healthcare providers is recommended to inform parents and assist with decision-making before the birth of a child with anticipated poor prognosis. In the setting of a low-income country, like Mongolia, attitudes of healthcare providers towards resuscitation of high-risk newborns are unknown. The purpose of this study was to examine the attitudes of healthcare providers regarding ethical decisions pertaining to non-initiation and withdrawal of neonatal resuscitation in Mongolia. A questionnaire on attitudes towards decision-making for non-initiation and withdrawal of neonatal resuscitation was administered to 113 healthcare providers attending neonatal resuscitation training courses in 2009 in Ulaanbaatar, the capital and the largest city of Mongolia where 40% of deliveries in the country occur. The questionnaire was developed in English and translated into Mongolian and included multiple choices and free-text responses. Participation was voluntary, and anonymity of the participants was strictly maintained. In total, 113 sets of questionnaire were completed by Mongolian healthcare providers, including neonatologists, paediatricians, neonatal and obstetrical nurses, and midwives, with 100% response rate. Ninety-six percent of respondents were women, with 73% of participants from Ulaanbaatar and 27% (all midwives) from the countryside. The majority (96%) of healthcare providers stated they attempt pre-delivery counselling to discuss potential poor outcomes when mothers present with preterm labour. However, most (90%) healthcare providers stated they feel uncomfortable discussing not initiating or withdrawing neonatal resuscitation for a baby born alive with little chance of survival. Religious beliefs and concerns about long-term pain for the baby were the most common reasons for not initiating neonatal resuscitation or withdrawing care for a baby born too premature or with congenital birth-defects. Most Mongolian healthcare providers provide antenatal counselling to parents regarding neonatal resuscitation. Additional research is needed to determine if the above-said difficulty with counselling stems from deficiencies in communication training and whether these same counselling-related issues exist in other countries. Future educational efforts in teaching neonatal resuscitation in Mongolia should incorporate culturally-sensitive training on antenatal counselling. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12298 J HEALTH POPUL NUTR 2012 Sep;30(3):346-352